Transformative Pedagogy: Assessing the Role of English Language Instructors in Indian Higher Education Institutions - Dr .T. Raja Sekhar (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2008)
Various countries have established Quality Assurance (QA) models for their higher education institutions in response to their own national circumstances, as a customary practise for progress and advancement. India is not an exception. Periodically, the National Assessment and Accreditation Council (NAAC) of India has been publishing literature that offers valuable insights into the Indian experience with regards to quality assurance. Upon reviewing these documents, we discern that the government’s viewpoint on "Quality education" can be understood as the attainment of educational outcomes that align with societal needs while minimising associated expenses.Given the aforementioned concept, it is vital to investigate whether contemporary higher education institutions are truly suitable for the purpose of imparting the necessary knowledge and skills to students and meeting the needs of society. The presence of new students at our universities serves as evidence of the educational standard. As university teachers, it is our responsibility to implement the university curriculum and exert significant effort in shaping these students to meet global standards. The given context pertains to the notion that while we may be unable to alter the past experiences of students, there is potential to facilitate their transformation into competent global citizens. This paper examines the effectiveness of English language instructors in universities in facilitating transformation in students who have undergone the teaching and learning process.